Reading Disability and Behavior Problems - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The early characteristics of groups of children, aged 7 to 8 years, identified with reading disability (RD) only, behavior problem (BP) only, RD and BP, and neither RD nor BP, were compared by temperament and behavior indices, gathered in 5 periods between infancy and 6 years of age, at the Department of Psychology, University of Melbourne, Australia.